Knowledge, Attitude and Practice (KAP) of the Healthcare Professionals and Community towards Patient Counselling in Tertiary Care Hospital - Patil, Dhanraj; Shelar, Kiran; Korade, Gayatri; Rituraj, Prince; Mhaske, Rushika; Kizhakethil, Midhun Mathew (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Patient counselling is recognized as an integral component of healthcare services, providing essential guidance to patients. However, it has been observed that in India, practical attendance of designated patient education sessions is not emphasised. Therefore, the principal aim of this research endeavour was to evaluate the Knowledge, Attitude, and Practice of Healthcare Professionals (HCPs) and the Community towards patient education. Materials and Methods: This research aimed to assess the KAP of patient counselling among Healthcare Professionals (HCPs) and Patient Caregivers (PCs) in THF. A cross-sectional survey was conducted, utilizing a self-administered questionnaire. The study highlights variations in knowledge of patient counselling practices and represents the first comprehensive assessment of HCPs' knowledge and the community's perception of patient counselling. Results: The respondents consisted of 347 females (69.4%) and 153 males (30.6%), representing different professional cadres, including doctors (39.0%), nursing staff (59.4%), and Clinical Pharmacists (CP) (1.6%). Approximately 41.2% of the participants demonstrated a "Positive" attitude towards patient counselling. However, the community generally held a positive attitude towards patient counselling, highlighting areas for improvement and potential interventions to enhance patient care services. Conclusion: There was no significant variation in the knowledge of different categories of HCPs and facility levels about patient counselling. Encouragingly, the overall attitude of respondents towards patient education and counselling was positive. Based on the above, strategies are needed to build capacity of HCPs and awareness of community to enhance the interaction between physicians, clinical pharmacists and patients.
Keywords: Attitude and Practice; Clinical Pharmacist; Knowledge; Patient Counselling